2016
DOI: 10.1039/c6sc00419a
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed incorporation of atmospheric CO2: efficient synthesis of functionalized oxazolidinones

Abstract: CO2 at atmospheric pressure is used in two Pd-catalyzed multicomponent reactions to produce functionalized 5-methylene-1,3-oxazolidin-2-ones from propargylamines and aryl halides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(53 citation statements)
references
References 38 publications
(20 reference statements)
2
51
0
Order By: Relevance
“…In 2016, the Nevado group reported a palladium‐catalyzed three‐component reaction between propargylic amines, aryl iodides, and CO 2 (Scheme ) . A series of oxazolidin‐2‐ones that contained tetrasubstituted exocyclic C=C double bonds were readily accessed in a stereocontrolled fashion.…”
Section: Cyclization Reactions Of Propargylic Amines With Co2mentioning
confidence: 99%
“…In 2016, the Nevado group reported a palladium‐catalyzed three‐component reaction between propargylic amines, aryl iodides, and CO 2 (Scheme ) . A series of oxazolidin‐2‐ones that contained tetrasubstituted exocyclic C=C double bonds were readily accessed in a stereocontrolled fashion.…”
Section: Cyclization Reactions Of Propargylic Amines With Co2mentioning
confidence: 99%
“…Mono-and diarylsubstituted oxazolidinones from propargylic amines and CO2. 95 Other interesting substrates have been used for oxazolidinone synthesis, but not enantioselectively. In 2014, Repo and coworkers 34 reported 5-and 6-membered cyclic carbamates from racemic cyclization of various β-and γ-haloamines with CO2, and Soldi et al 96 reported intramolecular carboxylative cyclization of allylamines.…”
Section: Scheme 19mentioning
confidence: 99%
“…93,94 Nevado and coworkers have reported a Pd-catalyzed carboxylation of propargylic amines and aryliodides, giving mono-arylated oxazolidinones with complete E-selectivity (Scheme 20). 95 Also homodiarylated (Ar 1 = Ar 2 ) and heterodiarylated products (Ar 1 ≠ Ar 2 ) can be obtained by changing the reactions conditions. Note that any chiral products were prepared as racemic mixtures only.…”
mentioning
confidence: 99%
“…Nevado et al. have employed Pd nanocatalysts for the synthesis of oxazolidinones from propargylamines, aryl halides, and CO 2 . However, often very high pressure of CO 2 is necessary to achieve a high conversion level.…”
Section: Future Potentialmentioning
confidence: 99%